Analysis of Transportation Service Marketing Strategies In Facing Competition - Sinaga, Multiyani; Asyari, Asyari (Peneliti.net, 2025)
This study aims to analyze the transportation service marketing strategy implemented by PT. Sibuluan Indah Pratama in facing competition in Sibolga City. Increasing competition among transportation service providers has prompted companies to formulate appropriate strategies to survive and grow. The research method used is descriptive qualitative with a case study approach. Data was collected using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach to identify internal company factors. The research results indicate that the company is in Quadrant I of the SWOT analysis, which is a favorable position supporting the implementation of aggressive growth strategies. The strategies employed include leveraging a large fleet and branch network to expand the market and collaborating with external parties such as the government and organizations. On the other hand, the company also faces several challenges, such as an outdated fleet, lack of technology utilization, and the need to improve driver services. Therefore, the company is advised to improve service quality, update its fleet, and use digital technology to enhance efficiency and competitiveness. This study is expected to contribute to the development of marketing strategies, particularly in the transportation services sector.